ADJOURNMENT OF TRIAL IN CRIMINAL PROCEEDINGS FOR THE PURPOSE OF PROVIDING EACH OF THE STAGES OF PROVING - Ланцедова, Юлія Олександрівна; Степанківська, Наталія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article examines the legislative understanding of the stages of proving for the CPC of different countries of the post-Soviet space, traditional and innovative approaches to solving this problem in the context of finding the proper grounds for adjournment of the trial in criminal proceedings. Research methods: general scientific methods, a comparative legal method and a system of logical methods were applied in the work. Results: an innovative solution to the problem of consistency of proving is proposed in the form of seven stages and a number of elements of the procedure for working with sources of evidence and proving. Discussion: the importance of this innovative approach is revealed to solve other problems of proving in general and the problem of adjournment of the trial in particular: it is proposed to take part in the discussion on the development of a generally accepted solution to these problems.